Characteristics and significance of doublets on needle EMG. Issue 4 (2nd December 2016) - Lamb, Christopher J.; Rubin, Devon I.
ABSTRACT: Introduction: Voluntary doublets are electrophysiological phenomena thought to be associated with metabolic derangements or neuromuscular conditions. Methods: We prospectively studied 232 consecutive patients examined by a single examiner during routine electromyography (EMG) to determine the frequency of doublets in individual patients, specific muscles, neuromuscular conditions, electrolyte levels, and doublet characteristics. Results: Of 232 patients, 25 (10.7%) exhibited doublets. The mean age was 59 (52% men). Only 32 of 1, 303 (2.5%) muscles exhibited doublets. Lower extremity and paraspinal groups represented 91% of muscles with doublets. Doublet frequency grouped by EMG diagnoses was: ALS (3 of 11; 27.1%), myopathy (3 of 10; 30.0%), axonal polyneuropathy (7 of 29; 24.1%), and no disease (7 of 109; 6.4%). There were no differences in serum electrolytes between doublet and matched subjects. Conclusions: Doublets occur in approximately 10% of patients, more commonly in lower extremity and paraspinal muscles, and are not correlated with a specific metabolic abnormality or neuromuscular condition. Muscle Nerve 55 : 598–600, 2017